Right and left-sided infective endocarditis in an IV drug abuser - Maryam Nemati; Kristine Galang; Syung Min Jung (Greater Baltimore Medical Center, 2020)
Infective endocarditis (IE) involving multiple cardiac valves is uncommon and has more risk of complications. We present an interesting case of infective endocarditis involving both aortic and tricuspid valves, suspected based on clinical presentation. He is a 54-year-old male with history of intravenous drug abuse (IVDA) who presented with exertional dyspnea, fevers/chills, fatigue, and temporarily vision loss. On exam, he had a low-grade fever, systolic murmur, bilateral crackles in lungs, and left hemineglect. He had leukocytosis and elevated BNP. First EKG showed first-degree AV block. CT head showed a subacute stroke in the right posterior cerebral artery (PCA) distribution. Transthoracic echocardiogram revealed a large tricuspid valve vegetation. He developed a second-degree heart block and a transcutaneous pacemaker was placed. Due to high concern for aortic valve involvement, a transesophageal echocardiogram was done revealing a large mobile tricuspid valve vegetation and an aortic valve ring abscess. He underwent abscess debridement and replacement of the aortic and tricuspid valve. He was found to have a ventricular septal defect which was also repaired. He recently had antibiotics for presumed pneumonia that is likely the reason for negative cultures. He received an 8-week course of Ceftriaxone for culture negative infective endocarditis and subsequently recovered well. This case report highlights that, although rare, the presence of right and left sided IE is possible and suspicion of aortic valve involvement is crucial in the setting of AV nodal blocks and peripheral embolic events. In patients with progressive heart blocks, transvenous pacemaker placement and valve replacement should be considered immediately to prevent further morbidity and mortality.